Ketegangan Antarsukubangsa, Orang Bugis, dan Masalah ‘Penjelasan’ - Kathryn Robinson (Antropologi Indonesia, 2000)
Outbreaks of violence in eastern Indonesia in 1998 were characterized by attacks on migrants from Sulawesi. Anti-Bugis prejudice has a long history in the archipelago, but historically it has been expressed in differing ways. What explanations have been put forward for political/ethnic violence in Indonesia? By comparing the discussion of last year's conflict with that after the post-coup killings, for example, the author raises the question of 'what do we learn'? Is sociological logic adequate in these situations? In this article the author argues that at the foremost, we have to move beyond the reification of ethnic and religious difference, which produce their own mythic enchantment. Explanations of violence need to be grounded in specific historical analysis, in this case the recent history of Indonesian politics.